2004
DOI: 10.1126/science.1092963
|View full text |Cite
|
Sign up to set email alerts
|

Cubic AgPb m SbTe 2+ m : Bulk Thermoelectric Materials with High Figure of Merit

Abstract: The conversion of heat to electricity by thermoelectric devices may play a key role in the future for energy production and utilization. However, in order to meet that role, more efficient thermoelectric materials are needed that are suitable for high-temperature applications. We show that the material system AgPb(m)SbTe(2+m) may be suitable for this purpose. With m = 10 and 18 and doped appropriately, n-type semiconductors can be produced that exhibit a high thermoelectric figure of merit material ZTmax of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
1,202
5
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,792 publications
(1,287 citation statements)
references
References 15 publications
31
1,202
5
10
Order By: Relevance
“…One successful strategy for improving zT is to enhance the power factor S 2 / ρ through band engineering,2, 3, 4, 5, 6, 7 provided the carrier concentration is optimized 8. The other effective strategy is typified by minimizing the only one independent material property, the lattice thermal conductivity ( κ L ), through nanostructuring,9, 10, 11, 12, 13, 14, 15 liquid phonons,16, 17 and lattice anharmonicity 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…One successful strategy for improving zT is to enhance the power factor S 2 / ρ through band engineering,2, 3, 4, 5, 6, 7 provided the carrier concentration is optimized 8. The other effective strategy is typified by minimizing the only one independent material property, the lattice thermal conductivity ( κ L ), through nanostructuring,9, 10, 11, 12, 13, 14, 15 liquid phonons,16, 17 and lattice anharmonicity 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…Harman et al [4] reported values of ZT between 1.3 to 1.6 in PbSeTe/PbTe quantum dot superlattices. More recently Kanatzidis and co-workers found that bulk AgPb 18 SbTe 20 with internal nanostructures has ZT ≈ 2 at T = 800 K [5]. In nanocrystalline BiSbTe bulk alloys ZT reached the value 1.4 at T = 373 K [6].…”
Section: Introductionmentioning
confidence: 99%
“…A relaxation-time model for electrical carrier-interface scattering was developed to account for the fi ltering eff ect of low-energy electrons on transport properties. Tl x Pb 1-x Te [17] AgSbTe 2 [14] Ag-Pb-Sb-Te (LAST) [15] (GeTe) 1-x (AgSbTe 2 ) x (TAGS) [16] CsBi 4 Te 6 [12] Yb x Co 4 Sb 12 (skutterudites) [18] SiGe [19] Yb x Ba 8-x Ga 16 Ge 30 (clathrates) [25] Hf 0.6 Zr 0.4 NiSn 0.98 Sb 0.02 (half-Heusler) [24] Yb 14 Mn 1-x Al x Sb 11 (Zintl phase) [23] Temperature ( n-type (Mg 2 Si y Ge 1-y )-(Mg 2 Si 0.6 Ge 0.4 ) nanocomposites. Th e inspired work of Kanatzidis's group revealed that a new kind of intrinsic nano-inclusion, as shown schematically in Figure 3(k), formatted by the segregation of silver and antimony in the lead sublattice of PbTe, could achieve simultaneous phonon blocking and electron transmission.…”
Section: Nanostructural Approaches For Enhancing Thermoelectric Perfomentioning
confidence: 99%